In situ effect of a proanthocyanidin mouthrinse on dentin subjected to erosion (Journal of Applied Oral Science, 2021)
Proanthocyanidin has been shown to be efficient in inhibiting matrix metalloproteinases. Objective: The aim of this in situ study was to evaluate the protective effect of Proanthocyanidin-based mouthrinses either with naturally acidic or with a neutral pH applied on dentin subjected to erosion. Methodology: Eight volunteers wore one palatal device in two phases (7 days washout) with 16 samples per group (n=8). The groups under study were: First Phase/ G1 – 10% proanthocyanidin mouthrinse (pH 7.0, Experimental group 1 – Purified Grape Seeds Oligomeric Proanthocyanidins), G2 – 10% proanthocyanidin mouthrinse (pH 3.0, Experimental group 2 – Purified Grape Seeds Oligomeric Proanthocyanidins). Second Phase/ G3 – 0.12% chlorhexidine mouthrinse (pH 7.0, Positive control group), G4 – no previous treatment (Negative control group). Each device was subjected to 3 erosive cycles (5 minutes) per day for 5 days. Treatments with different mouthrinses were applied once after the second erosive challenge (5 minutes). Profilometry was used to quantify dentin loss (µm). Results: Data were analyzed by repeated measures of ANOVA followed by Fisher’s test (p<0.05). G1 (1.17±0.69) and G3 (1.22±0.25) showed significantly lower wear values with no statistical difference between them. G2 (2.99±1.15) and G4 (2.29±1.13) presented higher wear values with no significant differences between them. Conclusion: The 10% proanthocyanidin mouthrinse (pH 7.0) could be a good strategy to reduce dentin wear progression.